2016
DOI: 10.1002/2015gc006166
|View full text |Cite
|
Sign up to set email alerts
|

Crustal anisotropy beneath Pacific Ocean‐Islands from harmonic decomposition of receiver functions

Abstract: Crustal anisotropy beneath ocean islands can be attributed to preferentially aligned minerals, cracks, or dike structures. Stacked with harmonic weighting, receiver functions from permanent ocean‐island stations display evidence of strong and distinct anisotropy parameters in the underlying crust and underplated layer. We analyze data for 11 IRIS‐GSN stations in the Pacific Ocean. We observe the prevalence of two‐lobed receiver function (RF) amplitude variations with back‐azimuth, consistent with “slow” tilted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 94 publications
(254 reference statements)
8
42
1
Order By: Relevance
“…We have demonstrated that even underneath young oceanic crust (20-60 Ma), the seismic LAB depth can vary over a depth range of 40 km (Figure 10), also a recent study of ocean islands suggests that there is significant anisotropic layering in the crust and lithospheric mantle of these anomalous regions [Olugboji and Park, 2016]. We have demonstrated that even underneath young oceanic crust (20-60 Ma), the seismic LAB depth can vary over a depth range of 40 km (Figure 10), also a recent study of ocean islands suggests that there is significant anisotropic layering in the crust and lithospheric mantle of these anomalous regions [Olugboji and Park, 2016].…”
Section: Evaluation Of the Melt And Anisotropy Modelsupporting
confidence: 69%
See 1 more Smart Citation
“…We have demonstrated that even underneath young oceanic crust (20-60 Ma), the seismic LAB depth can vary over a depth range of 40 km (Figure 10), also a recent study of ocean islands suggests that there is significant anisotropic layering in the crust and lithospheric mantle of these anomalous regions [Olugboji and Park, 2016]. We have demonstrated that even underneath young oceanic crust (20-60 Ma), the seismic LAB depth can vary over a depth range of 40 km (Figure 10), also a recent study of ocean islands suggests that there is significant anisotropic layering in the crust and lithospheric mantle of these anomalous regions [Olugboji and Park, 2016].…”
Section: Evaluation Of the Melt And Anisotropy Modelsupporting
confidence: 69%
“…At high frequencies, the conversions from broad velocity gradients can be resolved [e.g., Olugboji et al, 2013], also thin melt layers or sharp interfaces can also be resolved at higher frequencies [e.g., Leahy and Park, 2005;Leahy and Collins, 2009;Leahy et al, 2012]. This technique is combined with the approach of harmonic decomposition [e.g., Levin and Park, 1998;Bianchi et al, 2010;Olugboji and Park, 2016] which allows recovery of periodic variations in amplitude with back azimuth of the receiver function traces, indicative of layered anisotropy or tilted interfaces at depth (e.g., section 3.2 and Figure 5). This technique is combined with the approach of harmonic decomposition [e.g., Levin and Park, 1998;Bianchi et al, 2010;Olugboji and Park, 2016] which allows recovery of periodic variations in amplitude with back azimuth of the receiver function traces, indicative of layered anisotropy or tilted interfaces at depth (e.g., section 3.2 and Figure 5).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Rychert et al () estimate Sp receiver functions, which typically involve lower frequencies than Ps receiver functions, to infer an underplated layer beneath the Galapagos Islands that extends to 37 ± 7‐km depth. Olugboji and Park () reported underplated layers beneath 11 ocean‐island stations within the Pacific Ocean basin, using a harmonic regression of Ps receiver functions over back azimuth to investigate anisotropic layering with frequency cutoff 1 Hz. With this low‐passed restriction, Olugboji and Park () typically inferred thick layers beneath their stations, roughly 30 km for the combination of crust and underplated layer.…”
Section: Seismic Evidence For Anisotropic Underplated Layersmentioning
confidence: 99%
“…In the case of Hawaii, data from ocean‐bottom seismometers have detected a sub‐Moho layer, attributed to magmatic underplating, that extends hundreds of kilometers from the loci of active hot spot volcanism (Leahy et al, ). Olugboji and Park () reported that the underplated layer at 11 hot spot islands contained anisotropy that weakly correlated with inferred stress directions at the time of island formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation